Delictological Approach to the Classification of Offenses: Theoretical and Legal Analysis Using the Example of Ukrainian Legislation - Sergey V. Petkov; Veronika N. Shkabaro; Oleh H. Bodnarchuk; Igor E. Ivanov; Oleksandr D. Kolomoiets (Indian Journal of Forensic Medicine & Toxicology, 2021)
The article analyses the problem of the concepts of crime and offense definitions, considers legal issues oftheir set of facts; based on the analysis of constitutional, administrative and criminal legislation, the criteriato differentiate offenses from homogeneous crimes are proposed; scientific views of lawyers are analysed;legislation improvement of the post-Soviet republics in delictology are proposed.